2019
DOI: 10.1149/2.1361914jes
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in the Electro-Oxidation of Thiourea on Platinum Electrode Studied by On-Line HPLC

Abstract: The oscillations in the electro-oxidation of thiourea on platinum electrode in perchloric acid were studied by the cyclic voltammetry and potentiostatic method combined with on-line HPLC. The effects of different scanning speed, initial concentration of thiourea and sampling on the current oscillations of thiourea were investigated, results showed that: (1) the lower scanning speed and higher initial concentration of thiourea facilitated the oscillations; (2) the sampling increased the oscillation current and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A schematic diagram of this device can be found in a previous paper. [9] For HPLC analysis, the mobile phase consisted of a mixture of methanol, acetonitrile, and 0.01 M hydrochloric acid (6 : 26 : 68, vol%). All the electrochemical experiments were carried out with a VSP‐300 electrochemical station (BioLogic).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A schematic diagram of this device can be found in a previous paper. [9] For HPLC analysis, the mobile phase consisted of a mixture of methanol, acetonitrile, and 0.01 M hydrochloric acid (6 : 26 : 68, vol%). All the electrochemical experiments were carried out with a VSP‐300 electrochemical station (BioLogic).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] A variety of studies have shown that abundant nonlinear dynamical phenomena occur in the TU oxidation process. [6][7][8][9] As an intermediate of such processes, the TU 2 2 + exhibits different valence changes and various products, including oxides and free radicals, as well as the occurrence of autocatalytic and hydrolysis reactions. [10][11] A. E. Bolzán et al applied voltammetry and rotating ringdisk electrode techniques to study electrochemical response of thiourea and formamidine disulphide on polycrystalline platinum electrode.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations